2011
DOI: 10.1371/journal.pone.0028043
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the 2009 Pandemic Influenza A (H1N1) Virus in Water and on Non-Porous Surface

Abstract: Knowledge of influenza A virus survival in different environmental conditions is a key element for the implementation of hygiene and personal protection measures by health authorities. As it is dependent on virus isolates even within the same subtype, we studied the survival of the 2009 H1N1 pandemic (H1N1pdm) virus in water and on non-porous surface. The H1N1pdm virus was subjected to various environmental parameters over time and tested for infectivity. In water, at low and medium salinity levels and 4°C, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 21 publications
9
80
0
1
Order By: Relevance
“…Compared with the classical icosahedral viruses, including the picornaviruses, the environmental persistence of influenza virus is less but not negligible (52)(53)(54). In order to persist within the infected host cell, the influenza virus requires flexibility of its envelope to enable dynamics in membrane curvature during the viral life cycle, including host cell receptor binding, viral fusion with the host endosome, and budding during viral assembly.…”
mentioning
confidence: 99%
“…Compared with the classical icosahedral viruses, including the picornaviruses, the environmental persistence of influenza virus is less but not negligible (52)(53)(54). In order to persist within the infected host cell, the influenza virus requires flexibility of its envelope to enable dynamics in membrane curvature during the viral life cycle, including host cell receptor binding, viral fusion with the host endosome, and budding during viral assembly.…”
mentioning
confidence: 99%
“…This result may be an artifact of how the human and swine viruses tested in our study were propagated; it has been shown that both human and avian viruses grown on MDCK cells are more stable at higher temperatures than are the same viruses when grown in chicken eggs (24). At higher temperatures, all the viruses assessed, regardless of their subtype and origin, were quickly inactivated, especially at temperatures higher than 28°C; this is similar to the reduction in persistence seen for a 2009 pandemic H1N1 and a 1999 seasonal H1N1 from Ͼ150 days at 4°C to just 2 days at 35°C (22). While swine viruses persisted significantly longer than human viruses at 10°C (P ϭ 0.045) and 23°C (P ϭ 0.010) in this study, such differences were not consistent across the broader range of temperatures evaluated, and given the small sample sizes, the statistical power is low.…”
Section: Discussionmentioning
confidence: 62%
“…To be transmitted and maintained, viruses must remain infectious. It has been well established that IAVs persist longest at cold temperatures (12,13,17,22,23); human and swine viruses analyzed in this study lasted longest at 4°C, and results were consistent with those previously reported for pandemic virus A/Paris/2590/2009 (H1N1), which had a reported Rt value of 178 days at 4°C (22). The swine and human viruses included in this study, however, demonstrated greater persistence at low temperatures than did a suite of viruses of avian origin that were previously analyzed (12).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the survival of poliovirus in water was historically extensively studied [16][17][18][19] before the number of studies declined in recent years in parallel with the eradication of the disease worldwide. On the other hand, there has been an increase in respiratory diseases linked to viruses carried by waterfowl, such as influenza [1,20,21], and studies on these viruses have been increasingly numerous. Likewise, following the terrorist threats of the early 2000s, more studies have been dedicated to potential biowarfare agents [6,22].…”
Section: Experimental Studies: Goals Methodsmentioning
confidence: 99%
“…It has been universally demonstrated that higher temperatures mean faster viral inactivation. At low temperatures above freezing, viruses may survive for extended periods of time, often longer than the duration of the study [18], and sometimes for several years [21]. At higher temperatures, the viral population will be reduced by several orders of magnitude in a few days [28].…”
Section: Factors Affecting Virus Survivalmentioning
confidence: 99%